Fatigue resistance design of rubberized asphalt mixture pavement under three-dimensional stress state. (8th November 2021) - Lv, Songtao; Tan, Li; Peng, Xinghai; Hu, Long; Liu, Hongfu; Yuan, Jiang; Wang, Shuangshuang
Highlights: The feasibility of the Miller yield criterion in rubberized asphalt mixture was discussed. A fatigue model based on the von mises stress was obtained. The design criterion under three-dimensional stress state was established. Abstract: With the promotion of sustainable development globally, it is a positive and feasible measure to put waste tires into road engineering, such as rubber asphalt pavement. Therefore, it is very significant to improve the accuracy of fatigue resistance design of rubber asphalt pavement structures. This work aims to truly characterize the fatigue resistance of rubberized asphalt pavement structure, and provides favorable conditions for the efficient utilization of waste rubber powder in asphalt pavement engineering. First, the strength tests under different stress status and loading rates were carried out, which set up the strength yield surface on account of the Miller yield criterion. The fatigue tests of rubberized asphalt mixture in various stress levels and stress state were carried out. Von mises stress was taken as the characteristic parameter of the fatigue equation, and a unified fatigue characteristic equation of rubberized asphalt mixture affected by individual stress states was developed through the routine fatigue test. Finally, combined with Miller yield criterion and fatigue unified equation, the fatigue resistance model of rubberized asphalt pavement structure under the three-dimensional stress state was conducted. The results indicate that: the established Miller strength yield surface can reasonably describe the three-dimensional failure characteristics of rubberized asphalt mixture. Besides, the unified model of fatigue properties of rubberized asphalt mixture only needs to be characterized by single parameter, which is a power function coefficient in the new fatigue equation, and the value is −6.021. Moreover, the fatigue resistance model of the rubberized asphalt pavement structure sufficiently considers the difference between the tension–compression strength and fatigue characteristics of rubberized asphalt mixture and the stress state correlation. This study improves the scientificity and reliability of structural resistance design, and provides help for predicting the fatigue life of rubberized asphalt pavement.